RETRACTED ARTICLE: Company financial path analysis using fuzzy c-means and its application in financial failure prediction - Liu, Jiaming; Wu, Chong (Journal of Business Economics and Management, 2018)
View retraction statement: Retraction notice to “Company financial path analysis using fuzzy c-means and its application in financial failure prediction” [Journal of Business Economics and Management, 19(1), 213-234, 2018].